Zalacca fruit consumption to reduce nausea and vomiting in trimester I pregnant women in Banjarnegara District - Umi Fajri; Dian Nirmala Sari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Introduction : Nausea and vomiting occur in 80-85% of pregnancies during the first trimester with annoying vomiting symptoms in 52%. The way to deal with nausea and vomiting is pharmacochemical by consuming fresh fruit, namely zalacca. In 100 mg of zalacca fruit contains B6 0.2 mg which can reduce nausea. Objectives : To  find out that zalacca fruit can reduce nausea and vomiting in pregnant women in the 1st trimester. Methods : The research used was a quasy experimental design with a pretest posttest control group design. The variables in this study were zalacca fruit, nausea and vomiting. The number of samples is 30 respondents. The treatment group received 100 mg of zalacca fruit and B6 3 x 10 mg per day for 10 days while the control group received anti-nausea therapy, namely B6 3 x 10 mg / day for 10 days, before the intervention, the control group and the treatment group would get pre-test (assessment of nausea and vomiting) and then continued with the intervention for 10 days and ended with a post test (assessment of nausea and vomiting). Data analysis was univariate, bivariate using the Repeated Measure Anova (Test of Between-Subjects Effect) test. Result :  Showed that there was an effect of consuming zalacca fruit to reduce nausea (p = 0.000) and vomiting with a value of p = 0.012. Conclusion : Consumption of 100mg zalacca can reduce nausea and vomiting in 1st trimester pregnant women.